Community Behavior in Choosing Health Services after the Covid-19 Pandemic - Supriyadi, Supriyadi; Zaini, Mad (GLOBAL HEALTH SCIENCE GROUP, 2023)
The decline in the number of visits at the FKTP Klnik Mitra Keluarga Sejahtera Sukowono after the COVID-19 pandemic in June 2022 was around 55% per month and tended to stagnate and even a downward trend in early 2023. So that it resulted in a decrease in the number of visits at Klnik and increasingly had an impact on public trust in services in the area around Sukowono Jember. This study aims to look at the behavior of choosing health services by the community in the post-Covid-19 pandemic period. This research method is an observational analytic research with a cross-sectional design. The sample size was 257 respondents with purposive sampling technique. Using questionnaire instruments and chi square test analysis and logistic regression test. Research Results Variables associated with behavioral patterns of choosing health services in this study are pain perception, accessibility, information, socioeconomics, and family support. Factors that influence the behavior of choosing health services are pain perception (p=0.026; Exp(B)=2.012), accessibility (p=0.019; Exp(B)=1.962), information quality (p=0.021; Exp(B)=1.974), socioeconomic (p=0.006; Exp(B)=0.149) and family support value (p=0.006; Exp(B)=0.149). Perception of illness, accessibility, quality of information are the factors that most influence the behavior of choosing health services during the post-COVID-19 pandemic.